Microclima na produção de alface hidropônica em ambiente protegido utilizando telas de sombreamento como subcobertura - Sales, Francisco Alexandre de Lima (2012)
The adequacy of the microclimate of greenhouses to the needs of crop, has become a very important factor for the proper development of protected crops, times and in certain internal temperatures rise and may reduce photosynthesis.For this alternative technologies can be used to suit the needs of temperatures cultures, such as the use of shading screens, particularly for reducing the temperature in the warmer periods of the day. Therefore, the objective of this study was to evaluate the effect of different types of shading screens installed inside the greenhouses, just below the roof, on the growth of two varieties of lettuce crisp (Marianne and Veronica), in a production system in NFT hydroponic (Laminar Flow Technique). The experiment was conducted in greenhouses covered with LDPE film of 150 micron, which had the following treatments: environment without using the screen as undercoverage (ST), ambient thermal reflector screen as undercoverage (TC), Environment shade cloth as black undercoverage (TP) and environment as undercoverage red screen (TV). To assess the environmental changes caused by the use of LDPE film and screens were installed in each greenhouse and an outdoor thermo-hygrometer data loggers that recorded the environmental variables (temperature and relative humidity) every 30 minutes throughout the period of Experimental. Subsequently, we calculated the accumulated degree days for each environment. To analyze changes in patterns of plant response to different environmental conditions, there were five samplings during the experiment, and randomly collected twenty plants per treatment. The plants were removed from the benches replaced by others coming from the stands replacement. After collecting the plants, they were brought to the laboratory for measurement of dry weight of root, stem and leaves, and leaf area. This information was used for estimating of variable morphological. The results indicated that the use of screens as undercoverage affected the environment inside the greenhouse, especially temperature and relative humidity, where the use of thermal reflector and black screens reduced the maximum temperature at 4.7 and 3.6 ° C, respectively, with the environment that was not on screen as undercoverage (ST). Regarding the accumulation of degree days, the environment and TV ST showed very similar behavior, however environments CT and VT had a lower thermal accumulation in relation to TS and TV. As for the morphological changes caused by environmental changes, we determined that the use of thermal reflector screens and black influenced, positively, the number of leaves, leaf number larger than 10 cm and the leaf area index. It was also observed that the variables, number of leaves, leaf number larger than 10 cm, leaf area index, absolute growth rate and net assimilation rate were adjusted, with high levels of determination, a sigmoidal equation with three parameters. While the variables, leaf weight, leaf area ratio, specific leaf area and relative growth rate showed a better fit 3rd degree polynomial. In general, the use of thermal reflector and black screens provided an improvement of some key factors to trade in plants (number of leaves greater than 10 cm and LAI), however, it is not possible to say that these conditions are significant for all seasons , making it necessary more study at other times of the year.